(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2020)
The study examines the individual investor’s intention effect of attention-grabbing stocks such as stocks in the news, stock experiencing high abnormal trading, and stocks with high returns. Attention driven trading results from an individual investor’s ability to process information when being exposed to a large amount of information. The study includes Google’s Search Volume Index (SVI) as a proxy for investor attention. Thus, preferences of certain stocks determine decision making after attention has determined the selected stock in which trading is increased.